Ženska v judovskem izročilu - Večko, Snežna (Edinost in dialog, 2014)
The paper aims to answer the question what a successful woman according to the Holy Scripture is like and what the biblical women could suggest the contemporary woman in this matter. Modern literature makes a connection with the Jewish women of the past in the way which transcends a simple viewpoint of their life as being supressed and robbed of options. It sees in them the diversity of power and complexitiy. Such an image has doubtlessly been built also on the Holy Scripture and other sources throughout history. It turns out that the woman of all ages, so also the one from the Holy Scripture, possesses the power with which she plans, obtains, keeps and guards the life values. They consist of the love of her husband, children, home and the realization of her personal gift of creativity. Its realization is largely dependent on the cultural factors of time and environment. Yet the woman has never been just a passive recipient of given facts and dictates. She was always a co-shaper of cultural standards. By the way of accepting, activating, transcending, opposing, breaking them, she has co-shaped the patterns of thinking, evaluating and acting.
Keywords: woman; ženske; Judaism; judovstvo; sveto pismo stare zaveze